PENDEKATAN ISLAM TERHADAP MANAGER - Al Azhar; Rusli, Sumiati (ADISAM PUBLISHER, 2025)
This research aims to investigate the impact of applying Islamic values and principles in the context of organizational management, specifically the role and responsibilities of a manager. Adopting a qualitative approach, this study analyzes the concept of management from an Islamic perspective and how it can be implemented in day-to-day managerial practices. Through in-depth interviews and literature review, this research identifies relevant and profound principles of Islamic management and evaluates how managers can integrate these values into their decision-making and operational actions. The Islamic approach to management is elucidated through concepts such as justice, business ethics, value-based leadership, and social responsibility. The findings of this research are expected to provide new insights into the significance of the Islamic approach in the context of modern management. Practical implications include guidance for managers to understand and implement Islamic management principles within their frameworks, aiming to strengthen the quality of decision-making and enhance the balance between organizational goals and the high moral values upheld in Islam